Evaluasi Kualitas Fungsional Aplikasi POS Alfamart dari Repository GitHub Menggunakan Standar Pengujian ISO/IEC 29119 - Muhammad Ishomi Dhiwa; Sahala Yudha; Chairul Anwar (PT Jurnal Cendekia Indonesia, 2025)
The utilization of open-source software from public repositories often lacks standardized quality assurance and testing documentation, posing potential functional failure risks during operational deployment. This study aims to evaluate the functional quality and technical feasibility of the